2012
DOI: 10.1155/2012/756284
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Analysis of Variation on Beef Tenderness Induced by Acute Stress in Angus Cattle

Abstract: Beef is one of the leading sources of protein, B vitamins, iron, and zinc in human food. Beef palatability is based on three general criteria: tenderness, juiciness, and flavor, of which tenderness is thought to be the most important factor. In this study, we found that beef tenderness, measured by the Warner-Bratzler shear force (WBSF), was dramatically increased by acute stress. Microarray analysis and qPCR identified a variety of genes that were differentially expressed. Pathway analysis showed that these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
1
21
2
1
Order By: Relevance
“…Recent evidence shows that genes involved in immune response and 552 regulation of metabolism in Angus cattle were associated with variation in beef 553 tenderness induced by acute stress, using cDNA microarray and quantitative real-time 554 PCR expression analysis [61]. We found increased levels of glycolytic (TPI1), 555 mitochondrial membrane (ATP5B) and glycosyltransferase (ST6GAL1) proteins in 556 DFD as compared to normal meats.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 86%
“…Recent evidence shows that genes involved in immune response and 552 regulation of metabolism in Angus cattle were associated with variation in beef 553 tenderness induced by acute stress, using cDNA microarray and quantitative real-time 554 PCR expression analysis [61]. We found increased levels of glycolytic (TPI1), 555 mitochondrial membrane (ATP5B) and glycosyltransferase (ST6GAL1) proteins in 556 DFD as compared to normal meats.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 86%
“…Regarding cytokines and chemokines, it has been found that they modulate different stages of muscle cell development [36], [37]. In a recent work, Zhao and collaborators (2012) [38] found evidence that RNA expression of genes involved with acute inflammatory response has high influence in meat tenderness in Angus cattle. They observed that chemokines and cytokines genes, including chemokine C-C ligand 8 present in our gene list (ENSBTAG00000014113, BTA19), were deregulated in animals submitted to a surgical procedure, which in turn showed higher Warner-Bratzler shear force in beef samples after slaughter compared to the control group, suggesting that they play important role in muscle metabolism, either in vivo or in postmortem proteolysis regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Data from our own group show that both sire breed and genetic merit for carcass weight affect the expression of genes regulating the somatotropic axis in muscle of cattle (Keady et al, 2011), with greater gene expression of IGF-1 and reduced transcript abundance of IGFBP3 in muscle potentially having a role in increased muscle growth. Whereas transcriptomic studies have been fundamental in the establishment of the molecular mechanisms regulating important traits in cattle (McCabe et al, 2012;Zhao et al, 2012), mRNA expression does not always refl ect corresponding proteomic abundance (Rogers et al, 2008). Consequently, proteomic studies examining large numbers of proteins simultaneously, including their posttranslational modifi cations (Rogers et al, 2008), offer a snapshot of the functional molecules of the cells under investigation.…”
Section: Introductionmentioning
confidence: 99%